Critical interpretation of hybridisation in Korean cinema - Jin, Dal Yong (Javnost (Ljubljana), 2010)
This paper examines the fundamental assumptions of the concept of cultural hybridity in understanding the swift growth of Korean popular culture, especially films. It investigates whether hybridity, as a cultural globalization perspective, has generated new possible cultures, which are free from western dominance, by analyzing the hybridized Korean films. Unlike previous studies emphasizing the crucial role of hybridisation in creating the third space, this paper empirically argues that the hybridisation process of the local popular culture is heavily influenced by Western norms and formats, and newly created local cultural products are rather representing Western culture, instead of unique local culture. It finally discusses the reasons why hybridity cannot adequately explain local cultures and identify some issues we have to consider in employing hybridity in interpreting globalisation.
Keywords: film; Južna Koreja; sociologija kulture; filmska industrija